TINJAUAN FIQH MUAMALAH TERHADAP PERJANJIAN CAGAK HUTANG - Ativa Riani; Elsy Renie (Institut Agama Islam Negeri Batusangkar, 2022)
The purpose of the discussion of this article is to find out the use of cagak hutang and a review of fiqh muamalah in Nagari Simpang Sugiran, Guguak District, Lima Puluh Kota Regency. The type of research that the author uses is field research, namely field research that is qualitative in nature. Sampling technique the author uses a snowball sampling technique. The data collection technique that the author uses is interviews, documentation and observations related to the agreement on cagak hutang in Nagari Simpang Sugiran, Guguak District, Lima Puluh Kota Regency. From the research that the author has done, it shows that the debt reserve in Nagari Simpang Sugiran, Guguak District. People use cagak hutang in the form of living (moving) goods and inanimate (immovable) goods. Cagak hutang is used because they have no other choice, what is used as cagak hutang is the only thing that can be given by the debtor as collateral or foreclosure on his debt. In practice, most of the use of forked debt is in the control of the murtahin, he enjoys the results and uses the benefits of debt fork for his own benefit. The implementation of cagak hutang in Nagari Simpang Sugiran, Guguak District, Lima Puluh Kota Regency has become a habit and has raised social aspects in society that can overcome economic problems. This activity has become an alternative for the community to avoid hunger and poverty because it has helped the community's economy. In Islam, habits that have been carried out continuously and repeatedly in a society can be used as a source of law. However, in practice, the habit of using cagak hutang in Nagari Simpang Sugiran, Guguak District, Lima Puluh Kota Regency is included in a fasid habit or is contrary to the arguments of the Qur'an and Hadith.